Plasma nitric oxide concentrations during dialysis induced hypotension - (:unkn) unknown (My University, 2001)
Objective: We investigated the levels of nitric oxide (NO) and its role in hypotensive episodes in hemodialysis (HD) patients. Methods: Twelve HD patients (6 male, 6 female, mean age 47.1 ± 2.7 years, mean duration of HD 44.5 ± 8.1 months) were included in the study. Patients who demonstrated ≥20% reduction in mean arterial blood pressure (MAP) during any time period of HD were classified as the hypotensive group, and those who did not demonstrate ≥20% reduction were classified as the nonhypotensive group. NO levels were estimated from NO metabolites (NOx) measured by Greiss reaction in blood samples collected at baseline, 30, 60, 90, 120, 180 and 240 minutes of HD. Results: Five of 12 patients demonstrated hypotensive episodes during HD. NOx concentrations were similar at the beginning and at the end of HD in hypotensive and nonhypotensive groups. NO concentrations decreased continuously throughout the HD. Percent decline of NO were also similar in both groups during the entire study period. There was no correlation between the NO concentrations and MAP at baseline and at the end of HD. Conclusion: We suggest that NO could not be responsible for hypotensive episodes in dialysis patients. Further studies should be performed to investigate the factors contributing to hypotensive episodes in these patients so that further therapeutic strategies may be evaluated and applied.
Keywords: Hemodialysis; Hypotension; Nitric oxide